Development of a Tumor Bonding Model Based on Cohesive Properties for Improving Breast Tumor Classification Using Rotation Elastogram - Espindola-Rojas, D (IEEE Computer Society, 2025)
In quasistatic ultrasound elastography, the rotation elastogram allows the visualization of the rotation ability of benign breast tumors such as fibroadenomas. This means that rotation fill-in, which represents the rotation average value within the lesion, has become a benignity marker that can be used as a tumor classification imaging tool. However, its handheld application under clinical conditions introduces fluctuations that make it difficult to interpret correctly. The physical nature behind these fluctuations is not fully understood and cannot be captured using a single Coulombian friction model. In this context, we propose including a cohesive term in the interfacial contact law to model the dependence of the stress field on the rotation fill-in signature. First, we performed in-vitro experiments on gelatin phantoms for loosely and firmly bonded elliptical shape inclusions inclined at ≈45° with respect to the compression axis. An axial compression of 2% is applied at different ultrasound probe angles to introduce a lateral gradient in the stress field. Finite element simulations are then systematically performed and compared directly with the experimental results. We found that an appropriate selection of the cohesive term and friction coefficient globally captures the experimental tendency. An interfacial contact force analysis is necessary to define a more suitable frictional model in order to understand the underlying physics in the rotation fill-in signature. © 2025 IEEE.